Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1960
DOI: 10.1111/j.1365-2672.1960.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

THE DIFFERENTIATION OF PSEUDOMONAS FROM OTHER GRAM‐NEGATIVE BACTERIA ON THE BASIS OF ARGININE METABOLISM

Abstract: SUMMARY: Of 391 Gram‐negative bacteria isolated from chicken meat spoiled at a low temperature and classified by the commonly used methods, 156 were considered to be Pseudomonas and 188 Achromobacter, and 47 others belonged to the coli‐aerogenes group or remained unclassified. A test for the production of alkaline conditions in an arginine medium incubated under a vaseline seal gave positive results for 155 of the Pseudomonas isolates, and negative results for 1 Pseudomonas and all the 188 Achromobacter strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
145
0
3

Year Published

1962
1962
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(154 citation statements)
references
References 30 publications
1
145
0
3
Order By: Relevance
“…From studies on DNA homology and base composition, De Ley et al (1966) concluded that P. pavonacea and P. rubescens should be removed from Pseudornonas, while the inclusion in the genus of P. diminuta and P. iodinum was considered doubtful. The generic status of P. diminuta was queried by Rhodes (1958) and Thornley (1960), while P. iodinum is exceptional in being non-motile, oxidasenegative and Gram-variable or Gram-positive. This organism is included in the current (1964) NCIB catalogue as a coryneform organism.…”
Section: Discussionmentioning
confidence: 99%
“…From studies on DNA homology and base composition, De Ley et al (1966) concluded that P. pavonacea and P. rubescens should be removed from Pseudornonas, while the inclusion in the genus of P. diminuta and P. iodinum was considered doubtful. The generic status of P. diminuta was queried by Rhodes (1958) and Thornley (1960), while P. iodinum is exceptional in being non-motile, oxidasenegative and Gram-variable or Gram-positive. This organism is included in the current (1964) NCIB catalogue as a coryneform organism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the present state of our knowledge it seems wise to determine the flagellar pattern of any Gram-negative rod that is being classified. Because the determination of flagellar pattern is difficult and time-consuming, and because the classification of non-flagellate forms and forms which show a variation in the type of flagellation they display (Leifson & Hugh, 1953 Thornley, 1960), and the modified cytochrome oxidase test (Ewing & Johnson, 1960), in which only polarly flagellate rods give positive results, are promising in this respect. It should be noted that the Aeromonas strains studied in the present work gave late or negative results in the original form of the cytochrome oxidase test.…”
Section: Aeromonasmentioning
confidence: 99%
“…The arginine tests described by Sherris et al (1959) and by Thornley (1960) were not used with the organisms studied here, It seems that these tests are of considerable value in distinguishing between Pseudommus and peritrichously or nonflagellate bacteria, but of less value in separating Pseudomow from other polarly flagellate bacteria between which there appear to be only quantitative differences.…”
Section: Pseudomonasmentioning
confidence: 99%
“…These were: oxidase production (Kovacs, 1956); growth in nutrient (Harrigan and McCance, 1966); catalase production; glucose oxidation (Hugh and Leifson, 1953); production of arginine dihydrolase (Thornley, 1960); gluconate oxidation, (Shaw and Clarke, 1955); pyocyanin and pyorubrin production in Difco Pseudomonas P Agar and in the medium of Frank and DeMoss (1959), the identity of pyorubrin being confirmed spectrophotometrically (Palumbo, 1972); production of fluorescent pigment in Difco Pseudomonas F Agar; acid production from 16 carbohydrates in an agar medium containing only 0.2% (w/v) peptone and with bromthymol blue as the pH indicator; urease production (Stewart, 1965); gelatinase and caseinase production (Cowan, 1974); elastase production (Morihara, 1964); lipase production in Oxoid Tributyrin Agar; egg-yolk reaction (Esselmann and Liu, 1961); haemolysis in Oxoid Tryptone Soya Agar containing 5% (v/v) defibrinated sheep or horse blood (Burroughs Wellcome).…”
Section: Methodsmentioning
confidence: 99%